Clinical Efficacy of a Multimodal Integrated Medicine Protocol in Fibromyalgia Syndrome: A Retrospective Study Based on Real-World Evidence - Rosaria Ferreri (Journal of Alternative, Complementary & Integrative Medicine, 2026)
Fibromyalgia Syndrome (FMS) is a complex chronic pain condition characterized by central sensitization, neuroendocrine dysregulation, and systemic neuroinflammation